Final account preparation in construction industry: competencies and challenges of quantity surveyors / Nur Khairina Khairul Hisham ... [et al.] - Khairul Hisham, Nur Khairina; Othman, Mohd Khairul Fitri (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Final account in a construction project is prepared to show the final cost of the project that has been completed by a contractor. Preparation of the final account involves reporting the final cost of construction works, and it is one of the services that must be provided by quantity surveyors. Quantity surveyors display their competencies in preparing a final account by producing the certificate without being disputed and in a timely manner. However, issues and problems usually occur when rolling the final account, often related to quantity surveyors' competencies. This paper aims to study challenges faced and competencies displayed by quantity surveyors in relation to the final account preparation. An extensive literature review of previous research and content analysis of court cases reported in the Malayan Law Journal were conducted to identify challenges and competencies of quantity surveyors in preparing a final account.